Pemberdayaan Masyarakat Melalui Kuliah Kerja Nyata (KKN) di Desa Poreh, Kecamatan Lenteng, Kabupaten Sumenep (Lembaga Pengembangan Kinerja Dosen, 2025)
Community Service (KKN) is a means of implementing the Tri Dharma of Higher Education (Tri Dharma) in the aspect of community service. This article describes the implementation of KKN Group 17 of Universitas PGRI Sumenep in 2025, located in Poreh Village, Lenteng District, Sumenep Regency. The program lasted one month (July 23–August 23, 2025) and employed a participatory approach. The program included six main programs (village logo creation, MSME product digitalization, August 17th competition, parenting outreach, ecobricks, coloring competition) and four supporting programs (community service, healthy exercise, cheerful Quranic study group, and study mentoring). The implementation method consisted of initial observation, village deliberation-based planning, program implementation with active community involvement, and joint evaluation. Results indicated increased environmental awareness, the formation of a village visual identity, the development of MSME digital literacy, increased community participation, and increased motivation for learning among children. Issues that emerged included low community participation, limited facilities, and program sustainability. Solutions are sought through cultural approaches, program adaptations, and the formation of community mobilization groups. This article emphasizes that KKN plays a strategic role in community empowerment when implemented contextually, adaptively, and sustainably.